REGULATIONS REGARDING DANGER CONDITIONS APPLIED IN INDONESIA - Susdarwono, Endro Tri; Wicaksono, Pamungkas (Wacana: Jurnal Ilmu Sosial dan Ilmu Politik Interdisiplin, 2023)
The state of danger is always associated with danger to the state. If the safety of the state is threatened, the threat is considered a danger to the state. This research is normative in nature, using a statute approach, namely by examining the constitution and laws and regulations relating to legal issues, as well as a conceptual approach. This study concludes that there are four legal rules that serve as the umbrella for the implementation of an emergency for the territory of Indonesia, namely Regulation SOB 1939, Law Number 6 of 1946, Law Number 74 of 1957 and Perpu Number 23 of 1959. The Regulation of SOB 1939 distinguishes the level of danger into two i.e. in SvO and SvB states. Law Number 6 of 1946 does not regulate the level of danger. This is different from the next two hazard regulations. Law Number 74 of 1957 distinguishes a state of danger into two, namely a state of emergency and a state of war, while Perpu No. 23 of 1959 distinguishes the level of a state of danger into three, namely the level of civil emergency, military emergency and a state of war.